Analisis faktor yang memengaruhi kemampuan auditor dalam mendeteksi kecurangan: Kajian literatur sistematis - Simanjuntak, Rebeca boru; Mare, Rita Nian Jubata (Journal of Accounting and Digital Finance, 2025)
This study identifies and analyzes factors influencing auditors' fraud detection capabilities through a systematic literature review following PRISMA protocol. A comprehensive review was conducted on 23 primary studies (2013-2025) from 856 initially identified articles through systematic screening across leading academic databases. Thematic analysis identified two primary categories affecting fraud detection capabilities. Internal factors include professional skepticism, which correlates positively with fraud detection effectiveness, specific audit experience, knowledge of fraud schemes, analytical abilities, and training programs. External factors encompass client transaction complexity, regulatory environment, client pressure, and audit technology capabilities. Findings reveal significant evolution from traditional checklist-based approaches toward integration of advanced analytics and artificial intelligence. Analytics technology demonstrates capability to increase anomaly detection by up to 34%, while potentially reducing auditor professional skepticism. Digital transformation creates demand for new competency development integrating human judgment with technological capabilities. The research contributes to developing a holistic conceptual framework that integrates multidimensional factors within modern business complexity contexts, offering strategic recommendations for regulators, firms, educational institutions, and practitioners.